Prevalence of coccidiosis in Andaman local goat and its metaphylaxis in tropical island ecosystem - DE, A K; PERUMAL, P; MUNISWAMY, K; AHMED, S K ZAMIR; KUNDU, A; SUNDER, JAI; ALYETHOD, R R; RAVI, S K; BHATTACHARYA, D (The Indian Journal of Animal Sciences, 2021)
This study reports the prevalence of coccidiosis in Andaman local goat, a native goat breed of Andaman and Nicobar Islands, India. The duration of study was one year. Maximum oocyst output was seen in kids of